2001
DOI: 10.1128/aem.67.10.4603-4609.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Nucleotide Sequencing, and Functional Analysis of a Novel, Mobile Cluster of Biodegradation Genes from Pseudomonas aeruginosa Strain JB2

Abstract: We have identified in Pseudomonas aeruginosa strain JB2 a novel cluster of mobile genes encoding degradation of hydroxy-and halo-aromatic compounds. Nineteen open reading frames were located and, based on sequence similarities, were putatively identified as encoding a ring hydroxylating oxygenase (hybABCD), an ATP-binding cassette-type transporter, an extradiol ring-cleavage dioxygenase, transcriptional regulatory proteins, enzymes mediating chlorocatechol degradation, and transposition functions. Expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 66 publications
1
36
0
Order By: Relevance
“…An uncharacterized activity was also reported in a salicylate-grown strain of Moraxella (33). However, very recently a four-gene cluster corresponding to and closely homologous to nagAaGHAb has recently been identified in close physical association to genes for chlorobenzoate catabolism (17). The gene products have S5H activity, but the surrounding DNA is completely devoid of any residues of associated NDO-like genes (17).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An uncharacterized activity was also reported in a salicylate-grown strain of Moraxella (33). However, very recently a four-gene cluster corresponding to and closely homologous to nagAaGHAb has recently been identified in close physical association to genes for chlorobenzoate catabolism (17). The gene products have S5H activity, but the surrounding DNA is completely devoid of any residues of associated NDO-like genes (17).…”
Section: Discussionmentioning
confidence: 96%
“…However, very recently a four-gene cluster corresponding to and closely homologous to nagAaGHAb has recently been identified in close physical association to genes for chlorobenzoate catabolism (17). The gene products have S5H activity, but the surrounding DNA is completely devoid of any residues of associated NDO-like genes (17). Whereas we suggested that the nag oxygenase cluster arose by insertion of nagGH into a classical nah-like operon (12), this finding suggests that the four constituent S5H genes may also have an independent evolutionary history of their own.…”
Section: Discussionmentioning
confidence: 99%
“…The 5Ј end of a second open reading frame was deduced downstream of the dxnB2 gene. This partial open reading frame encodes a fragment of 311 amino acid residues that shares sequence identity with salicylate hydroxylases (e.g., 65% amino acid sequence identity to the ␣ subunit of salicylate hydroxylase from Pseudomonas aeruginosa JB2 [16]). This result is consistent with DxnB2 being involved in dibenzofuran catabolism, as salicylate would be one of the products of the hydrolase-catalyzed reaction in such a pathway.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the plant genes/enzymes involved in 2,3-DHBA and 2,5-DHBA synthesis are unknown. However, based on bacterial pathways, it is possible that isochorismatase catalyzes the formation of 2,3-DHBA directly from IC (Rusnak et al, 1990), and hydroxylation of SA could be performed by a monoxygenase similar to those identified in Pseudomonas and Ralstonia (Hickey et al, 2001 and references therein).…”
Section: Conversion To Dihydroxybenzoatesmentioning
confidence: 99%